Spatial analysis - Kent, J. T. (John T.); Mardia, K. V. (Wiley series in probability and statistics, 2022)
This book provides insight into the statistical investigation of the interdependence of random variables as a function of their proximity in space and time. Interest in this area is being fuelled by the growing need to analyse data from many fields of application."--